Spotlight on hot carriers in halide perovskite luminescence - Lim, Melvin Jia Wei (2022)
Harnessing hot carriers’ (HC) excess energy is an attractive approach to surpass the Shockley-Queisser limit. Halide perovskites possess desirable slow HC cooling properties for developing next-generation solar cells. Their HC cooling properties on the ultrafast timescale are well-reported using a myriad of techniques. However, there remains a significant gap between the manifestations of such ultrafast phenomena into the steady state, which is crucial towards translation into real-world efficiency enhancements. Here, we illuminate the connection between these two realms in their steady-state photoluminescence spectra with a unified model that retrieves essential HC metrics like carrier temperature and thermalization coefficient under non-equilibrium conditions. Our findings reveal that perovskites’ thermalization coefficients are an order of magnitude lower than incumbent absorbers. Importantly, our direct approach deepens our understanding of HC contributions to efficiency enhancements and enables wider accessibility to the HC research community, which will help accelerate the development of perovskite HC solar cells.